Green Gains: The Role of Environmental Initiatives and Intellectual Capital in Enhancing Firm Value in Emerging Markets - Sinaga, Ferdinand I.P; Saputra, Dian (E-Jurnal Akuntansi; Vol 34 No 12 (2024), 2024)
This study explores how intellectual capital management and environmental sustainability contribute to enhancing firm value in competitive markets. It addresses a critical knowledge gap by examining the interplay between sustainability, innovation, and firm value in emerging markets, with integrated reporting considered as a moderating variable. Through panel regression analysis of 252 observations within the consumer cyclicals sector from 2021 to 2023, the findings reveal that environmental performance has a significant and positive impact on firm value. In contrast, intellectual capital does not exhibit a direct influence on firm value. Furthermore, integrated reporting weakens the relationship between environmental performance and firm value but does not moderate the link between intellectual capital and firm value. These results provide practical insights for firms seeking to refine their sustainability strategies in competitive markets and contribute to the academic discourse on the role of integrated reporting as a moderating factor in the nexus of sustainability, innovation, and value creation.